Polyanilines with Pendant Amino Groups as Electrochemically Active Copolymers at Neutral pH - Marmisolle, Waldemar A.; Gregurec, Danijela; Moya, Sergio; Azzaroni, Omar (ChemElectroChem, 2015)
One of the most promising fields of application of polyaniline (PANI)-based modified electrodes is the construction of biosensors. However, PANI itself is not electroactive in neutral media. This problem can be solved by copolymerization of aniline with other monomers. Herein, we present a study of the electrosynthesis and electrochemical performance of copolymer films of 3-aminobenzylamine and aniline. These films are both stable and electroactive in acid and neutral media. They can even be employed as mediators of ascorbic acid oxidation, showing variable electrocatalytic activity depending on the copolymer composition. The presence of different proportions of pendant amino groups was confirmed by using XPS. These groups are responsible for the increased electroactivity in neutral solution. The copolymer films studied here can be used as versatile building blocks in the construction of bioelectroactive assemblies.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Aminobenzylamine; Ascorbic acid; Copolymers; Polyaniline; X-ray photoelectron spectroscopy